(untitled) (Ukrainian Journal of Ophthalmology, 2025)
This article reviews the causes, pathogenesis, and major manifestations of chiasmal syndrome. In addition, it reviews the methods for diagnosing the condition, and the course of the syndrome in patients with various chiasmal-and-sellar disorders such as pituitary adenoma, craniopharyngioma, tuberculum sellae meningioma, and skull base aneurysm. The principle neuro-ophthalmological symptoms include decreased visual acuity, bitemporal visual field defects, and development of descending optic nerve atrophy. Early detection of ophthalmological symptoms is of critical importance for timely neurosurgical treatment.